2022
DOI: 10.1016/j.sjbs.2021.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of methanolic extract of green tea against Thioacetamide-Induced liver injury in Sprague Dawley rats

Abstract: Ethnopharmacological relevance Since ancient times, herbal medicines have been applied in the treatment of cancer. Tea, derivative from the dried leaves of Camellia sinensis (L.) Kuntze plant is the most popular beverage globally after water and is available in various forms. Green tea has been expansively investigated for its beneficial properties of cancer prevention and therapy. The goal of the research: The current study was conducted to evaluate the hepaprotective character of methanolic gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
(64 reference statements)
6
19
0
Order By: Relevance
“…However, the re-exposure test results, which were reassessed using an established and strict criterion, showed a negative causality for these two herbs (Teschke et al, 2015). Chaassociated hepatotoxicity was also once reported (Percevault et al, 2021), but on the other hand, evidence was found to support the hepatoprotective effects of its active compounds, L-theanine (Wang et al, 2020b;Wang et al, 2020c;Zhang et al, 2021;Chen et al, 2022a;Hamad Shareef et al, 2022;Wu et al, 2022). Moreover, chuan xiong and sheng jiang were reported to exhibit hepatoprotective effects (Lu et al, 2015;Amin et al, 2021;Yaghubi Beklar et al, 2021;Bekkouch et al, 2022;Guo et al, 2022).…”
Section: Summary Of Resultsmentioning
confidence: 94%
“…However, the re-exposure test results, which were reassessed using an established and strict criterion, showed a negative causality for these two herbs (Teschke et al, 2015). Chaassociated hepatotoxicity was also once reported (Percevault et al, 2021), but on the other hand, evidence was found to support the hepatoprotective effects of its active compounds, L-theanine (Wang et al, 2020b;Wang et al, 2020c;Zhang et al, 2021;Chen et al, 2022a;Hamad Shareef et al, 2022;Wu et al, 2022). Moreover, chuan xiong and sheng jiang were reported to exhibit hepatoprotective effects (Lu et al, 2015;Amin et al, 2021;Yaghubi Beklar et al, 2021;Bekkouch et al, 2022;Guo et al, 2022).…”
Section: Summary Of Resultsmentioning
confidence: 94%
“…TAA is a potent hepatotoxic agent used widely to induce acute liver toxicity in an experimental rodent model by interfering in the nuclear transport of RNA from the nucleus to the cytoplasm and increases free radicals leading to membrane injury [27,28]. TAA is a potent hepatotoxicant and undergoes bioactivation to thioacetamide sulphoxide by microsomal enzyme CYP2E1 and thioacetamide-S, S-dioxide [28,29]. Cell signaling inhibitors, such as TKIs, are essential in chemotherapy treatments [30].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological (H & E staining) and Masson's Trichrome staining, and immunostaing displayed the repressing effect of feeding with pinostrobin, which could be owing to its capability to prevent hepatocyte propagation, as designated by down-regulation of PCNA staining. Similarly, Shreef et al, (2021) exposed that green tea potentially inhibited the progression of liver cirrhosis, down -regulation of PCNA proliferation [48]. Jadaun et al, (2019) stated that pinostrobin inhibits proliferation and induces apoptosis in cancer stem-like cells through a reactive oxygen species-dependent mechanism [54].…”
Section: Discussionmentioning
confidence: 99%
“…showed Flavonoids from the leaves and twigs of Lindera sericea potent free radical scavenging and α-glucosidase inhibitory activities[71] Taha et al, (2012). demonstrated that Turnera diffusa possesses anti-ulcer activity, which could be attributed to lipid peroxidation inhibitory, immunomodulatory and anti-oxidant mechanisms of arbutin avonoid[72] Shareef et al, (2021). showed that green tea potentially inhibited the progression of liver cirrhosis, prevented oxidation of hepatocytes, recovered SOD and CAT enzymes, condensed MDA and reduced cellular in ammation[48].TAA induces in ammatory response that initiates a dynamic chain of immune responses associated with the release of vast amounts of in ammatory cytokines such as TNF-α and IL-6, which in turn produce increased quantity of ROS(Wei et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation